(untitled) - Dighton, John (Boca Raton, 2005)
The Fungal Community: Its Organization and Role in the Ecosystem, Third Edition addresses many of the questions related to the observations, characterizations, and functional attributes of fungal assemblages and their interaction with the environment and other organisms. This edition promotes awareness of the functional methods of classification over taxonomic methods, and approaches the concept of fungal communities from an ecological perspective, rather than from a fungicentric view. It has expanded to examine issues of global and local biodiversity, the problems associated with exotic species, and the debate concerning diversity and function. The third edition also focuses on current ecological discussions - diversity and function, scaling issues, disturbance, and invasive species - from a fungal perspective. In order to address these concepts, the book examines the appropriate techniques to identify fungi, calculate their abundance, determine their associations among themselves and other organisms, and measure their individual and community function. This book explains attempts to scale these measures from the microscopic cell level through local, landscape, and ecosystem levels. The totality of the ideas, methods, and results presented by the contributing authors points to the future direction of mycology.
Keywords: Fungal communities,Fungi